Feminisms and internationalism - Sinha, Mrinalini; Guy, Donna J.; Woollacott, Angela (Blackwell, 1999)
This book addresses the theme of the history of internationalism in feminist theory and praxis, covering such topics as the historical concept of internationalism within feminism and womena s movements; the nature of historical shifts within feminist movements, and challenges to internationalism within feminism by women of colour and by women from colonised or formerly colonised countries.